Patient-Based Ratio Method for Permanent Zone Donor Area Calculation in Hair Transplant - Sudhanshu Punia; Aakanksha Goel; Amit Gupta (Indian Journal of Plastic Surgery)
Introduction Most common type of hair loss is androgenetic alopecia. Orentreich's donor dominance theory and the definition of safe donor area are the theoretical foundation of modern hair transplantation. In safe donor area no progression of permanent hair loss occurs. Its knowledge is important to prevent loss of transplanted hair. Estimation is not tailored to every patient, also in early stages, the margins are assumed to be free from future hair loss. Our study is an attempt to find and establish a relationship between safe zone dimensions and other standard scalp dimensions, and effectively predict the complete safe zone in early stages of hair loss.